Does Playing Experience Improve Coaching? An Exploratory Study of Perceptual-Cognitive Skill in Soccer Coaches - Grundel, Anna; Schorer, Jörg; Strauss, Bernd; Baker, Joseph (Frontiers in Psychology, 2013)
In many sports, it is common for top coaching positions to be held by former players; however, despite the natural progression in many sports for skilled players to become high-level coaches, we have little understanding of how playing may develop useful skills for coaching. In this study we considered perceptual-cognitive skill across groups of high and low skilled soccer players and soccer coaches. A range of perceptual-cognitive variables was measured in an attempt to capture the diverse skills related to expertise in sport and coaching. Generally, results highlighted similarities between coaches and players on some tasks and differences on others.